Development of Probabilistic Life Cycle Cost Model for Electric Chillers - Hasbullah, Nurhamizah (2018)
Life-cycle cost (LCC) analysis is a very common terms in engineering practice. It is used as a decision making tool. The demand of accuracy in estimating cost for system or equipment is really essential for the industries’ survival. LCC can be estimated using two approaches which are deterministic approach and probabilistic approaches. Deterministic approach had been practiced by various industries as it is simpler and required less data in performing the estimation compared to probabilistic approach. However, deterministic approach might not represent the actual phenomena of the system since it neglected the uncertainties in the input variables. Probabilistic approach is more structured and comprehensive since it can handle the uncertainties and provide the most accurate LCC estimation. Due to such situation, probabilistic LCC analysis of electric chiller is developed in this study. A comparison of the deterministic approach and the probabilistic approach of LCC is conducted and the results showed that there are some significant difference in the output for the two approaches. Last but not least, sensitivity analysis is performed in order to know which parameters is the key driver to the net present value (NPV) of LCC. Operation cost, maintenance cost and the replacement cost are found to be the key driver for the LCC estimation. However, this study only cover the effect of electric chiller on long-term budget and there is no LCC comparison between chillers conducted.